Laborious Transformations: Plants and Politics at Bogor Botanical Gardens - Weber, Andreas; Wille, Robert-Jan (Studium, 2019)
Contributors to this theme issue examine the history of the life sciences at the Botanical Gardens in Bogor (Kebun Raya Bogor) in Indonesia. Each of the essays in this theme issue, focusses on a major transformation which the garden, its networks, and staff underwent in the nineteenth and twentieth centuries. Next to summarizing individual contributions, this introductory essay familiarizes readers with more recent scholarship in the field. Taken together, our theme issue suggests that the practice of the life sciences at the Gardens can be best analyzed as the outcome of historical processes of coordination and competition in which different disciplines, communities, networks not only in insular Southeast Asia but also other parts of the world played a formative role.